Analysis of Radio Resource Schedule in LTE eMBMS - Feng Zhou; Hui Liu (Dianxin kexue)
The LTE service eMBMS was focused on, including the architecture and advantages. Furthermore, the wireless technologies and radio resource schedule were discussed and analyzed.